ANALISIS KANDUNGAN VITAMIN A PADA DAUN PAKU-PAKU (Diplazium escelentum (Retz.)Sw.) BERDASARKAN PROSES PEMASAKAN - Yuliana Souhaly; M Nur Matdoan; S I. A. Salmanu (BIOPENDIX, 2018)
Background: The nails are plants that are often consumed by the community because they are effective in curing various diseases such as cough, asthma, fever, headache, diarrhea, and dysentery. Different cooking processes can affect the nutritional content of a food ingredient, one of which is vitamin A. Method: This type of research is comparative, namely to compare the content of vitamin A found in ferns (Diplazium esculentum (Retz) Sw.) Based on the cooking process, namely boiling, steaming and stirring. Location of analysis of vitamin A content in the Basic Chemistry laboratory of the Faculty of Mathematics and Natural Sciences, Pattimura University. The subjects of the study were 4 g of ferns extract, each of which was carried out based on the cooking process, namely stir-fry, boiled and steamed. Results: There is an effect of the cooking process on the content of vitamin A on ferns. The highest vitamin A content is found in the type of stir-fry cooking which is as much as 0,0594%, the type of steamed cooking is 0,0442% and the type of boiled cooking is 0,0243%. Sauteed vegetables have relatively low water content than those boiled or steamed. Conclusion: The highest content of vitamin A in vegetable ferns (Diplazium escelentum (Retz.) Sw.) Was found in the cooking process of the type of stirring with a vitamin A content of 0.0594 with a duration of 10 minutes